Capacity building and sustainable development efforts of national population commission, Awka, Anambra State - Nwagbala, Stella Chinelo; Edibo, Musa David; Ejiogu, Samuel Anodi; Obijiaku, Chimamkpa Promise (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study explored the relationship between capacity building and sustainable development efforts of the National Population Commission, Awka, Anambra State, Nigeria. Specifically, it examined the relationship between technological upgrade and accountability, it also determined the relationship between skills enhancement and resource efficiency of the National Population Commission, Awka, Anambra State. Methods: The study employed a survey research design. The population of the study was 190. Hypotheses were tested with Pearson Product Moment Correlation Coefficient with the aid of Statistical Package for Social Sciences (SPSS, version 27). Hypothesis one revealed that there is a significant positive relationship between technological upgrade and accountability of the National Population Commission, Awka, Anambra State with r = 0.876, n = 190, and p-value of 0.000 (p<0.05). Results: Hypothesis two showed that there is a positive significant relationship between skills enhancement and resource efficiency of the National Population Commission, Awka, Anambra State with r = 0.647, n = 190, and p-value of 0.015 (p<0.05). Limitations: The researcher encountered problems during the data collection process. The researcher was faced with an uncooperative attitude of some respondents by not providing answers to the questionnaire.   Contribution: This study contributes to the existing body of knowledge by providing empirical evidence on the significant positive relationships between technological upgrade and accountability and skills enhancement and resource efficiency in the National Population Commission, Awka, Anambra State. This study provides novel insights into effective population management strategies in Southeastern Nigeria.